2018
DOI: 10.3390/atmos10010007
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Mechanisms of Megadroughts over Eastern China during the Last Millennium: A Model Study

Abstract: The variability and mechanisms of multi-decadal megadroughts over eastern China during the last millennium were investigated using a control, full-forcing, and four sensitivity experiments from the Community Earth System Model (CESM) Last Millennium Ensemble (LME) archive. The model simulated megadroughts have comparable magnitudes and durations with those derived from reconstructed proxy data, although the megadroughts are not temporally synchronous. In all experiments, the megadroughts exhibit similar spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…A megadrought is usually defined as a persistent drought event with a duration longer than a decade (Coats et al, 2013; Ault et al, 2014; Cook et al, 2016). In this study, we chose the definition of megadrought as a period with precipitation anomalies (relative to the long term average across the 850-1850) less than 0 for 11 years and less than 1 standard deviation for at least 1 year (Ning et al, 2019). To be consistent with the reconstructed data, the simulated regional area-averaged precipitation anomalies are first 10-year running averaged before identifications of megadroughts.…”
Section: Definition Of Megadroughtmentioning
confidence: 99%
See 2 more Smart Citations
“…A megadrought is usually defined as a persistent drought event with a duration longer than a decade (Coats et al, 2013; Ault et al, 2014; Cook et al, 2016). In this study, we chose the definition of megadrought as a period with precipitation anomalies (relative to the long term average across the 850-1850) less than 0 for 11 years and less than 1 standard deviation for at least 1 year (Ning et al, 2019). To be consistent with the reconstructed data, the simulated regional area-averaged precipitation anomalies are first 10-year running averaged before identifications of megadroughts.…”
Section: Definition Of Megadroughtmentioning
confidence: 99%
“…Due to the large heat capacity, sea surface temperatures (SSTs) can influence the large-scale atmospheric circulations, and ultimately induce the decadal megadroughts in eastern China through influencing the EASM and EAWM (Ning et al, 2019). Previous studies (e.g., Yang et al, 2017) also suggest that SSTA over the tropics and North Pacific Ocean affect the decadal variability of precipitation over the eastern China by regulating the EASM, inducing the decadal variability in the south-north dipole pattern of precipitation over the eastern China.…”
Section: Origins Of the Circulation Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought events have increased in frequency and intensity in several regions of the planet in recent decades [1][2][3][4][5][6][7][8][9][10][11]. According to [12], while droughts represented only 4% of total economic losses (US$124 billion) in the period of 1998-2017, research conducted by Centre for Research on the Epidemiology of Disasters (CRED) in 2011 [13] related to 2481 disasters where information was available, when considering the impact of disasters according to their type, found that droughts cause significantly greater losses on national economies than other types of disasters, with almost 40% of droughts studied provoking damage equal to or greater than 0.5% of the gross domestic product (GDP) of the country where they occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also found that volcano-induced droughts usually persist longer over the ocean than the land [13].Eastern China is a typical monsoon domain, which is severely impacted by extreme drought events [15,16]. Some studies found that many drought events in the world are triggered primarily by internal variability of climate system [17][18][19]. Meanwhile, external forcings such as strong volcanic eruptions can also cast significant effects on the droughts over the Eastern China [2].…”
mentioning
confidence: 99%